2017
DOI: 10.1017/s0029665116002810
|View full text |Cite
|
Sign up to set email alerts
|

Lessons on dietary biomarkers from twin studies

Abstract: Metabolomic and microbiome profiling are promising tools to identify biomarkers of food intake and health status. The individual's genetic makeup plays a significant role on health, metabolism, gut microbes and diet and twin studies provide unique opportunities to untangle gene–environment effects on complex phenotypes. This brief review discusses the value of twin studies in nutrition research with a particular focus on metabolomics and the gut microbiome. Although, the twin model is a powerful tool to segreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 58 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…Efforts to replicate dietary biomarkers are still in their nascent stages; however, a recent observational study replicated 63 previously identified diet-metabolite associations and validated several putative dietary biomarkers identified in prior feeding studies [42]. Finally, investigators have begun to leverage twin studies in combination with dietary metabolomics and microbiome data in order to untangle complex gene-environment effects [43].…”
Section: Nutritional Metabolomicsmentioning
confidence: 99%
“…Efforts to replicate dietary biomarkers are still in their nascent stages; however, a recent observational study replicated 63 previously identified diet-metabolite associations and validated several putative dietary biomarkers identified in prior feeding studies [42]. Finally, investigators have begun to leverage twin studies in combination with dietary metabolomics and microbiome data in order to untangle complex gene-environment effects [43].…”
Section: Nutritional Metabolomicsmentioning
confidence: 99%